Bulbourethral dorsal onlay buccal mucosal graft urethroplasty - William Harrison; Kapilan Ravichandran; Devang Desai (Urology Video Journal, 2024)
Objective: Urethral strictures are a challenging problem that can have a significant impact on a patient's urinary function, sexual health, and quality of life. Buccal mucosal graft urethroplasty is the gold standard for long-segment or complex urethral strictures. This video submission aims to provide a visual manuscript on performing dorsal onlay buccal mucosal graft urethroplasty with the skilled hands of a fellowship-trained reconstructive urologist. In addition, there is an inclusion of a case series to demonstrate its effectiveness and outcomes. Methods and Surgical Procedure: A 67-year-old male with a non-obliterative fibrous stricture at the bulbourethra underwent a dorsal onlay buccal mucosal graft urethroplasty to improve his obstructive lower urinary tract symptoms and maintain erectile function. The study aimed to determine the success rate of the surgery in restoring urinary function, as well as assessing its effects on quality of life, sexual function, and patient satisfaction. Prospective data was collected on all patients undergoing the surgery, including pre- and post-operative uroflowmetry, IPSS, IIEF-5 questionnaires, and a modified PROM satisfaction survey. Complications were also recorded. The study was conducted by a reconstructive fellowship-trained consultant urologist specializing in urethroplasty at a regional center. Results: 32 patients underwent dorsal onlay urethroplasty between 2017 and 2022. The preoperative flow rates had an average Qmax of 8.65 mL/s and Qmean of 5.57 mL/s. The follow up was up to 36 months. Qmax average at 12 months follow up was 22 mL/s. IPSS improved and IIEF-5 scores were preserved. There were minimal complications, with one patient experiencing incontinence and one having overactive bladder symptoms. Patient satisfaction scores showed an increase over time, with 87 % of patients satisfied at 3 months, 94 % at 6 months, and retained at 94 % at 12 months. Conclusions: The success rate was 87.9 %, with 4 cases of recurrence, which increased to 97 % after redo urethroplasty. Objective measurements of urinary flow and quality of life consistently showed improvement over time, with preservation of erectile function. Limitations include the small sample size and incomplete follow-up due to the regional nature of the centre. A video submission demonstrating the procedure may aid trainees and fellows interested in urethroplasty training.